Perceptual threshold of apparent source width in relation to the azimuth of a single reflection - Johnson, Dale; Lee, Hyunkook (The Journal of the Acoustical Society of America, 2019)
An investigation into the perceptual threshold of apparent source width (ASW) in relation to a single reflection azimuth was performed in binaural reproduction. In the presence of a direct sound, subjects compared the ASW produced by a single 90° reference reflection against ASW produced by a test reflection with a varying angle for four reflection delay times between 5 and 30 ms. Threshold angles were found to be approximately 40° and 130°, and did not appear to be dependent on delay time. It was also found that these threshold angles were associated to saturation in [1-IACCE3] versus reflection azimuth.